Enhanced Li‐Storage of Ni3S2 Nanowire Arrays with N‐Doped Carbon Coating Synthesized by One‐Step CVD Process and Investigated Via Ex Situ TEM. Issue 49 (23rd October 2019) - Yao, Zhujun; Zhou, Linming; Yin, Haoyu; Wang, Xiuli; Xie, Dong; Xia, Xinhui; Gu, Changdong; Tu, Jiangping
Abstract: In this work, a facile strategy for the construction of single crystalline Ni3 S2 nanowires coated with N‐doped carbon shell (NC) forming Ni3 S2 @NC core/shell arrays by one‐step chemical vapor deposition process is reported. In addition to the good electronic conductivity from the NC shell, the nanowire structure also ensures the accommodation of large volume expansion during cycling, leading to pre‐eminent high‐rate capacities (470 mAh g −1 at 0.05 A g −1 and 385 mAh g −1 at 2 A g −1 ) and outstanding cycling stability with a capacity retention of 91% after 100 cycles at 1 A g −1 . Furthermore, ex situ transmission electron microscopy combined with X‐ray diffraction and Raman spectra are used to investigate the reaction mechanism of Ni3 S2 @NC during the charge/discharge process. The product after delithiation consists of Ni3 S2 and sulfur, suggesting that the capacity of the electrode comes from the conversion reaction of both Ni3 S2 and sulfur with Li2 S. Abstract : A one‐step chemical vapor deposition method is used to construct N‐doped carbon coated Ni3 S2 core/shell nanowire arrays (Ni3 S2 @NC) for Li ion storage. Positive advantages including large surface area and good electronic conductivity are obtained and lead to excellent high‐rate capacities (385 mAh g −1 at 2 A g −1 ) and outstanding cycling stability (91% retention after 100 cycles at 1 A g −1 ).